The Survival of the Script: Disavowal and the Persistence of the Symbolic Order in The Last One - Oktariza, Dodi; Syofyan, Donny (Universitas Muara Bungo, 2025)
This study provides a psychoanalytic exploration of Alexandra Oliva’s novel The Last One (2016), examining the protagonist Zoo’s psychological endurance through a global pandemic. By utilizing a qualitative symptomatic reading of the text, the research investigates how Zoo maintains her equilibrium by adhering to the